Strawberry as a health promoter: an evidence based review. Issue 5 (13th May 2015) - Giampieri, Francesca; Forbes-Hernandez, Tamara Y.; Gasparrini, Massimiliano; Alvarez-Suarez, José M.; Afrin, Sadia; Bompadre, Stefano; Quiles, Josè L.; Mezzetti, Bruno; Battino, Maurizio
<x xml:space="preserve">Abstract</x> The health effects of strawberry bioactive compounds depend on the activation and modulation of several genetic and molecular mechanisms.